Optimal management of wetlands: Quantifying trade-offs between flood risks, recreation, and biodiversity conservation - Birol, Ekin; Hanley, Nick; Koundouri, Phoebe; Kountouris, Yiannis (American Geophysical Union, 2009)
This paper employs a simple choice experiment to estimate the value of management options for the Bobrek wetland in Poland. The local public's valuation of several wetland management attributes, including flood risk reduction, biodiversity conservation and improvement of recreational access, are investigated. A latent class model is estimated to account for heterogeneity in the wetland management choices of the local public. The results reveal that there is considerable heterogeneity among the local public as two distinct segments are identified. For both of the segments, flood risk reduction, in the ranges considered, is more important than the other two attributes. The results of this study are expected to assist policy makers in undertaking effective flood risk reduction measures and formulating efficient, equitable and sustainable wetland management policies in accordance with the European Union's Water Framework Directive (2000/60/EC).